The relative contributions of MNTB and LNTB neurons to inhibition in the medial superior olive assessed through single and paired recordings - Roberts, Michael T.; Seeman, Stephanie C.; Golding, Nace L. (Frontiers in Neural Circuits, 2014)
The medial superior olive (MSO) senses microsecond differences in the coincidence of binaural signals, a critical cue for detecting sound location along the azimuth. An important component of this circuit is provided by inhibitory neurons of the medial and lateral nuclei of the trapezoid body (MNTB and LNTB, respectively). While MNTB neurons are fairly well described, little is known about the physiology of LNTB neurons. Using whole cell recordings from gerbil brainstem slices, we found that LNTB and MNTB neurons have similar membrane time constants and input resistances and fire brief action potentials, but only LNTB neurons fire repetitively in response to current steps. We observed that LNTB neurons receive graded excitatory and inhibitory synaptic inputs, with at least some of the latter arriving from other LNTB neurons. To address the relative timing of inhibition to the MSO from the LNTB vs. the MNTB, we examined inhibitory responses to auditory nerve stimulation using a slice preparation that retains the circuitry from the auditory nerve to the MSO intact. Despite the longer physical path length of excitatory inputs driving contralateral inhibition, inhibition from both pathways arrived with similar latency and jitter. An analysis of paired whole cell recordings between MSO and MNTB neurons revealed a short and reliable delay between the action potential peak in MNTB neurons and the onset of the resulting IPSP (0.55 ± 0.01 ms, n=4, mean ± SEM). Reconstructions of biocytin-labeled neurons showed that MNTB axons ranged from 580 to 858 µm in length (n=4). We conclude that while both LNTB and MNTB neurons provide similarly timed inhibition to MSO neurons, the reliability of inhibition from the LNTB at higher frequencies is more constrained relative to that from the MNTB due to differences in intrinsic properties, the strength of excitatory inputs, and the presence of feedforward inhibition.